Perancangan Media Infografis SOP Keselamatan Kerja (K3) Pada Lingkungan Industri Manufaktur - Daniel M Simbolon; Bambang Tri Wardoyo; Ekananda Haryadi; Menul Teguh Riyanti; Wegig Murwonugroho; Yosua Reydo Respati; Dikdik Adikara Rachman; Tommy Hari Prihatanto; Leonardus Aryo Gitoprakoso Widyarto; Meily Cristina (Lembaga Pengembangan Kinerja Dosen, 2026)
Occupational Health and Safety (OHS) is a crucial aspect in manufacturing industries due to the high risk of workplace accidents caused by heavy machinery, chemical substances, and intensive production activities. Companies usually provide Standard Operating Procedures (SOP) as safety guidelines; however, SOPs are often delivered in long textual formats that are less engaging, making workers reluctant to read or difficult to understand quickly. This study aims to design an infographic-based SOP media as an effective visual communication tool to improve workers’ understanding of safety procedures. The research applies a qualitative method with a design approach through workplace observation, interviews with HSE personnel, literature review, and design validation using questionnaires. The results produce infographic media in the form of posters and signage presenting PPE usage procedures, hazard warnings, and evacuation steps using safety color codes, icons, and readable typography. The conclusion indicates that infographic SOP media is more effective than text-based SOP because it improves readability, comprehension, and workers’ memory of safety procedures.